A5.4 Prevalence of comorbidities in Paget's disease of the bone a single centre report. (13th February 2015) - Deaconu, C; Groşeanu, L; Iorgoveanu, V; Borangiu, A; Opriş, D; Săulescu, I; Bojincă, V; Negru, M; Constantinescu, C; Berghea, F; Abobului, M; Vlad, V; et al.
Abstract : Background and objectives: Paget disease (PD), also known as osteitis deformans, is characterised by single or multiple bone site alteration, including accelerated osteoclast-mediated resorption followed by increased low quality bone production. This process results in a disorganised, unsteady structure that may lead to bone deformity. This condition affects elderly adult population, with a slightly higher predominance in males and it is thought to have important genetic determinants. The association of comorbid conditions places a burden on the patients and imposes regular monitoring. The present study aims to evaluate associated medical conditions in patients suffering from PD. Methods: We retrospectively identified 39 patients who were diagnosed with PD, based on clinical presentation, plain x-rays, scintigraphy or when necessary biopsy or bone turnover markers' detection. For the study group we noted the presence of cardiovascular disorders – hypertension, ischaemic heart disease or rhythm abnormalities such as atrial fibrillation. Median body mass index (BMI) was calculated. Neurologic conditions namely hearing loss, Parkinson's disease or cerebral stroke history were taken into account, as well as type 2 diabetes and prostate adenoma. Tobacco use was also assessed for the study group. Development of neoplasia was reviewed. Information was gathered from patients' clinical charts over a period of one year. Results: Out of the 39 patients included in the study lot, 64.1% were males and 35.9% of female gender (1.7:1 ratio) with a mean age of 65.67 years, who were mainly diagnosed on the basis of clinical and radiographic assessment (97.4%). 7.6% had positive family history of PD. The polyostotic form of PD encountered in 26 patients (66%) is prevalent over the monostotic pattern (13, 33.3%). The most common affected sites were the hip in 71.0% of patients, skull (44.7%), femoral bone (26.3%) and the lumbar spine (21.05%). 61.5% of patients were hypertensive while 28.2% associated ischaemic heart disease. 27.6% were priorly diagnosed with atrial fibrillation. Mean BMI value was calculated at 27.7 kg/m². 12.8% of patients were hypoacusic, 5.1% suffered from a cerebral stroke and the same percentage were diagnosed with Parkinson's disease. 52% of males had prostate adenoma, 15.3% suffered from type 2 diabetes. 20.5% patients confirmed smoking status. Three patients developed neoplasia, namely squamous cell carcinoma, carcinoma of the breast and rectum with no correlation to disease duration. Conclusions: Taking into consideration the difficulties that PD brings with it, associated comorbidities tend to diminish further the health and quality of life in these patients. Therefore a complete medical check-up is recommended on each follow up visit in order to improve their status.